Pengaruh Pemberian Bronsunta terhadap Penurunan Tekanan Darah pada Pasien Hipertensi di Klinik Pratama - Saputri, Ratih Eka Pramita; Siregar, Afriyana; Podojoyo, Podojoyo (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2024)
Background: Hypertension or more often called high blood pressure is a condition when blood pressure exceeds normal limits, systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. The aim of this study was to determine the effect of giving baked brownies with breadfruit flour and potato flour on the blood pressure of hypertension sufferers at the Pratama Derisman Clinic. Methods: This research consisted of 2 stages, the first stage used a non-factorial completely randomized design with a Pre Test - Post Test with Control Group Design research design. The sample in this study was 60 hypertension patients without complications, taken by purposive sampling. Data analysis used the Friedman test and t-dependent test, Results: Based on the results of research that has been conducted on hypertensive patients at the Derisman Primary Clinic, it can be concluded that the average systolic blood pressure of hypertensive patients who received Bronsunta and the consumption of antihypertensive drugs in the treatment group was 157.87 mmHg before treatment and 157.10 mmHg after treatment. The mean diastolic blood pressure was 93 mmHg before treatment and 90 mmHg after treatment. The average blood pressure of hypertensive patients who only consumed antihypertensive drugs in the comparison group was 157.67 mmHg before treatment and 157.23 mmHg after treatment. The mean diastolic blood pressure was 91 mmHg before treatment and 92 mmHg after treatment. This means that baked brownies with the addition of breadfruit flour and potato starch have an effect on lowering blood pressure in hypertensive patients. Conclusion: Based on the research results, it can be concluded that baked brownies with the addition of breadfruit flour and potato flour have an effect on reducing blood pressure in hypertensive patients